2012
DOI: 10.1017/s1368980012001048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalences of overweight and obesity and their association with physical activity pattern among Iranian adolescents aged 12–17 years

Abstract: Objective: The objective of the present study was to investigate the prevalences of overweight and obesity and their association with physical activity pattern among adolescents in northern Iran. Design: A cross-sectional study. Setting: Babol, northern Iran. Subjects: A representative sample of 1200 adolescents aged 12-17 years was recruited. All selected adolescents were interviewed, their leisure-time and sport physical activities were collected by a standard Baecke questionnaire and their height and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Most available studies reported that screen time plays an important role in childhood overweight/obesity; however, numerous studies may only focused on the association between a single type of screen time and childhood overweight/obesity (Ajie & Chapman‐Novakofski, ; Guy et al, ; G. Zhang et al, ), which unlikely to reveal the influence of overall screen time on overweight/obesity. In addition, a study that included 13,094 youth produced the result that the combination of TV viewing and computer use was not as consistently associated with overweight/obesity as was TV viewing alone (Hajian‐Tilaki & Heidari, ). Thus, it is essential to study the effects of the different types of screen time as risk factors on childhood overweight/obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Most available studies reported that screen time plays an important role in childhood overweight/obesity; however, numerous studies may only focused on the association between a single type of screen time and childhood overweight/obesity (Ajie & Chapman‐Novakofski, ; Guy et al, ; G. Zhang et al, ), which unlikely to reveal the influence of overall screen time on overweight/obesity. In addition, a study that included 13,094 youth produced the result that the combination of TV viewing and computer use was not as consistently associated with overweight/obesity as was TV viewing alone (Hajian‐Tilaki & Heidari, ). Thus, it is essential to study the effects of the different types of screen time as risk factors on childhood overweight/obesity.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, about 10% of adolescents have the metabolic syndrome [16], 23% are overweight or obese and 18% engage in low levels of physical activity [17]. In a previous publication from this study, we showed that adolescent and early adulthood obesity were associated with the risk of diabetes in adulthood [18].…”
Section: Introductionmentioning
confidence: 76%
“…A total number of 155,839 children and adolescents up to 20 years old were included from the selected studies. [91011131417181920212223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586] Comparison of the overall estimates in different age group represents that the overweight and obesity prevalence for children between 6- and 12-year-old is minimum for boys and girls, but in all age categories the overweight girls prevalence are higher than boys while the obesity boys prevalence are higher than girls [Table 1]. …”
Section: Resultsmentioning
confidence: 99%